ANALISIS STRATEGI PENJUALAN PRODUK SEBAGAI SUATU EVALUASI KINERJA BAGIAN PEMASARAN PRODUK MOBIL PADA PT. AGUNG AUTOMALL DURI - Claudia Andhini Sofyan; Lie Othman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
PT. Agung Automall Duri is a main dealer of car Toyota which wasinaugurated on June 12, 2005. In addition to selling a wide variety of itemsToyota brand cars also provide spare parts and servicing services to serve everycustomer who ever did a purchase cars at PT. Agung Automall Duri. To maintainthe company continuing as a goal, achieving sales targets and business benefit,PT. Agung Automall Duri implement sales strategies to achieve these goals.Research conducted at PT. Agung Automall Duri aims to determine theimplementation of sales strategy, business companies improve sales volume andthe constraints faced by PT. Agung Automall Duri thorn in selling car products.Data obtained in writing scientific papers obtained by distributing questionnairesto some of the employees and customers of PT. Agung Automall Duri were chosenas respondents.Data analysis technique used is descriptive analysis techniques, whereafter the data is collected, the data can be classified according to the indicatorsused in this research. From the research that has been done, it is known that thesales strategy PT.Agung Automall Duri can be categorized "good enough". It canbe seen from the responses given by the respondents in the research. That is whyit is suggested that PT.Agung Automall Duri implement sales strategies to better,and minimize factors that cause a decline in sales.Key Word: Strategy, Selling, Marketing